Kurikulum Mata Pelajaran Bahasa Arab Pada Madrasah Tsanawiyah Dan Madrasah Aliyah Negeri Di Kota Bengkulu - Nur Hidayat (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
The curriculum is one of the many things that always get attention, because it is considered as the most dominant factor in the achievement of the success of the teaching and learning process, although that success is also inseparable from other factors. The significance of this research for faculties, especially the Arabic Language Education study program, is through this research the researcher wants to give an overview to the Arabic Education Study Program about the Arabic learning curriculum used in various schools, especially State schools in Bengkulu City. the results of this study can be used as material for the development of Arabic language education study programs. This research is expected to help students in finding reading sources so as to improve their quality.